Sistem Informasi Pengolahan Data Penyediaan Air dan Sanitasi Masyarakat (PAMSIMAS) berbasis Web - Acep Irham Gufroni; Cecep Muhamad Sidik Ramdani; Haikal Millah; Miftahul Habib Fachrurozi; Andi Nur Rachman (Journal of Appropriate Technology for Community Services, 2021)
The availability of clean water is a hope for the community to meet the needs of drinking sources and the availability of proper sanitation will prevent various diseases. So the government collaborates with villages in providing Community Based Drinking Water and Sanitation (PAMSIMAS). The PAMSIMAS program aims to increase the number of clean water facilities for communities in areas with low economic income levels. In the PAMSIMAS program in Tigaherang Village, Rajadesa District, Ciamis Regency, socialization steps are needed to the community to provide an understanding of clean water and sanitation, monitoring of clean water use and transparency of the PAMSIMAS program. To support its implementation, a Web-based Information System for Water Supply and Sanitation (PAMSIMAS) application design is proposed. This information system is expected to be able to optimize the performance and service of clean water for the community. Keywords: Community, PAMSIMAS Program (community based drinking water supply and sanitation), Information System.